‘Safe Sport Is Not for Everyone’: Equity-Deserving Athletes’ Perspectives of, Experiences and Recommendations for Safe Sport - Gurgis, Joseph John; Kerr, Gretchen; Darnell, Simon (Frontiers in Psychology, 2022)
There is a growing concern that the voices of athletes, and in particular, athletes from equity-deserving groups, are unaccounted for in the development and advancement of Safe Sport initiatives. The lack of consideration of the needs and experiences of diverse groups is concerning, given the existing literature outside the context of sport indicating that equity-deserving individuals experience more violence. As such, the following study sought to understand how equity-deserving athletes interpret and experience Safe Sport. Grounded within an interpretive phenomenological analysis, semi-structured interviews were used to understand how athletes with marginalised identities conceptualise and experience Safe Sport. Seven participants, including two Black male athletes, two White, gay male athletes, one Middle Eastern female athlete, one White, female athlete with a physical disability and one White, non-binary, queer, athlete with a physical disability, were asked to conceptualise and describe their experiences of Safe Sport. The findings revealed these athletes perceived Safe Sport as an unrealistic and unattainable ideal that cannot fully be experienced by those from equity-deserving groups. This interpretation was reinforced by reported experiences of discriminatory comments, discriminatory behaviours and systemic barriers, perpetrated by coaches, teammates, and resulting from structural aspects of sport. The findings draw on the human rights literature to suggest integrating principles of equity, diversity and inclusion are fundamental to safeguarding equity-deserving athletes.